Gender and Dialogue in the Rabbinic Prism - Kosman, Admiel; Levin, Edward (Berlin : De Gruyter, 2012)
The author applies the fields of gender studies, psychoanalysis, and literature to Talmudic texts. In opposition to the perception of Judaism as a legal system, he argues that the Talmud demands inner spiritual effort, to which the trait of humility and the refinement of the ego are central. This leads to the question of the attitude to the Other, in general, and especially to women. The author shows that the Talmud places the woman (who represents humility and good-heartedness in the Talmudic narratives) above the character of the male depicted in these narratives as a scholar with an inflate
Keywords: Women in rabbinical literature; Man-woman relationships; Masculinity -- Religious aspects -- Judaism; Rabbinical literature -- History and criticism; Psychoanalysis and religion; Judaism and psychoanalysis; Jewish philosophy; RELIGION / Judaism / Talmud; Electronic books